Everyday religion : an archaeology of protestant belief and practice in the nineteenth century - Kruczek-Aaron, Hadley (Co-published with The Society for Historical Archaeology., 2015)
This book will employ historical archaeological evidence to broadly examine the forces that fed the Second Great Awakening and how a range of communities responded to the activist religious fervor of the time.